Got milk? Got cybersecurity risks! Unraveling ransomware threats in the German dairy industry - Eduard Anton; Helena Aptyka; Frank Teuteberg (Organizational Cybersecurity Journal)
Purpose – This study aims to explore the vulnerabilities of the dairy industry to ransomware threats, focusing particularly on the upstream supply chain and applying routine activity theory (RAT) to understand the evolving dynamics of cybercrime in critical infrastructure sectors. Design/methodology/approach – Utilizing expert interviews and network analysis, this research investigates the exploitation of complex supply chain vulnerabilities by motivated offenders. It delves into the intricate interplay between digital threats and physical supply continuity. Findings – The study uncovers that ransomware threats transcend digital boundaries, manifesting in disruptions to physical operations and presenting significant risks to food security. It underscores the threat posed by the convergence of information technology (IT) and operational technology (OT), emphasizing the urgent need for heightened awareness and robust defenses against this substantial menace. Practical implications – Addressing cyber vulnerabilities in critical sectors like dairy ensures not only the security of operations but also safeguards broader societal interests such as food security. Collaboration and proactive measures are essential to mitigate potential social and economic disruptions caused by cyber incidents. Originality/value – This research fills a knowledge gap by shedding light on the nexus between cyber threats and supply chain resilience. It emphasizes the need for industries to adapt traditional defense mechanisms in the face of sophisticated digital adversaries.